THE EFFECT OF LEARNING FACILITIES ON STUDENTS' LEARNING MOTIVATION AT SMP ISLAM MUTHMAINNAH ENDE - Ainun Jariyah; Veronika Praja Sinta Mbia Wae; Maimunah H. Daud (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
Learning facility is one important item to support the learning process. This paper discusses the effect of learning facilities on students' motivation at SMP Islam Muthmainnah Ende. The sample of the research involved 46 students in class VII. The sampling technique used was purposive sampling. The research instruments were questionnaires and documentation, which were analyzed by simple linear regression analysis through SPSS version 21. The results indicate that hypothesis Ha was accepted and H0 was rejected because there was an effect of learning facilities on students’ learning motivation which, was indicate a significance value of 0.000. The magnitude of the effect of learning facilities on students’ learning motivation is shown by the coefficient of determination of R2 = 0.310 or 31%.